Intramuscular BoNT/A injections cause an inflammatory response in the muscle tissue of rats. (18th August 2021) - Pingel, Jessica; Pacolet, Alexander; Elfving, Betina; Ledri, Litsa N
Objectives: The purpose of the present study was to investigate whether intramuscular BoNT/A injections cause an systemic inflammatory response and a local inflammatory response in the muscle tissue. Methods: Thirty-two male Sprague Dawley rats treated with BoNT/A (i.m., 1IU) were divided in four groups, depending on the time of BoNT/A injection (2 days before, 1, 2, and 4 weeks before the experiment). Bio-Plex Pro Rat Cytokine 23-plex Multiplex Assay (Bio-Rad, USA). Results: Systemic inflammation: 17 cytokines (IL1-α ( p = 0.005), IL-1β ( p = 0.01), IL-2 ( p = 0.04), IL-4 ( p = 0.03), IL-6 ( p = 0.03), IL-10 ( p = 0.02), IL12(p70) ( p = 0.03), IL-13 ( p = 0.04), IL-17 ( p = 0.03), GM-CSF ( p = 0.03), INF-γ ( p = 0.03), MIP-1α ( p = 0.03), MIP-3α ( p = 0.04), RANTES ( p = 0.001), TNF-α ( p = 0.04), vascular endothelial growth factor ( p = 0.03), and MCP-1 ( p = 0.02)) showed significantly higher expression levels 2 days after intramuscular BoNT/A injections compared to other time points (1, 2, and 4 weeks). Local inflammation: 12 cytokines (IL-1β ( p = 0.02), IL-6 ( p = 0.002), IL-10 ( p = 0.02), IL-13 ( p = 0.04), IL-17 ( p = 0.02), TNF-α ( p = 0.001), GM-CSF ( p = 0.01), M-CSF ( p = 0.04), MIP-1α ( p = 0.04), MIP-3α ( p = 0.002), RANTES ( p = 0.02), and MCP-1( p = 0.004)) showed higher expression levels 2 and/or 4 weeks after intramuscular BoNT/A injections compared to the other time points (2 days and 1 week). Conclusion: Intramuscular BoNT/A injections result in a rapid systemic inflammatory response that only lasts a couple of days. At the same time, intramuscular BoNT/A injections cause an inflammatory response locally in the muscle with significantly higher cytokine levels 2 and/or 4 weeks after injections.